Hubungan Personal Hygiene dan Sanitasi Lingkungan dengan Angka Kejadian Kecacingan (Soil Transmitted Helminth) Pada Petani Sayur di Kelurahan Maharatu Kecamatan Marpoyan Damai Kota Pekanbaru - Rafiqi Ulfa Ali; Zulkarnaini Zulkarnaini; Dedi Affandi (Dinamika Lingkungan Indonesia, 2016)
Abstrak: Personal hygiene and environmental sanitation is an important factor in the health care effort to avoid infection worms. Research has been conducted on vegetable farmers in Sub District of Marpoyan Damai Maharatu Pekanbaru City in March - May 2015 with a total sample of 50 people. The result showed that the majority of workers in the village vegetable worm disease Maharatu positive experience with this type of Ascaris lumbricoides and including minor infections. There is a relationship use of Personal Protective Equipment (PPE), health nails, wash hands, clean water, latrine quality and sewage with the incidence of the disease in Sub Maharatu worms.